Lidocaine Modulates Cytokine Production and Reprograms the Tumor Immune Microenvironment to Enhance Anti-Tumor Immune Responses in Gastric Cancer - Wu, Yi-Ying; Chen, Ming-Shan; Chen, I-Chun; Wu, Feng-Hsu; Liao, Tsai-Ling; Wen, Hsiao-Wei; Nielsen, Brent L.; Liu, Hung-Jen (International journal of molecular sciences, 2025)
Lidocaine, a local anesthetic, has been shown to modulate immune responses. This study examines its effects on cytokine production in peripheral blood mononuclear cells (PBMCs) from healthy donors and tumor-infiltrating immune cells (TIICs) from gastric cancer patients. PBMCs from healthy donors and TIICs from gastric cancer patients were treated with lidocaine. Cytokine production was assessed using flow cytometry and cytokine assays, with a focus on IFN-γ, IL-12, IL-10, TGF-β, and IL-35 levels. Cytotoxicity against primary gastric cancer cells (PGCCs) was also evaluated. Lidocaine inhibited IFN-γ production in CD8+ PBMCs and IL-12 in CD14+ PBMCs while increasing anti-inflammatory cytokines (IL-10, TGF-β, IL-35) in CD4+CD25+ and CD14+ cells. In TIICs, lidocaine enhanced IFN-γ and IL-12 production in CD8+ and CD14+ cells while reducing IL-10, TGF-β, and IL-35 levels, promoting an M1-like phenotype in macrophages. Mechanistically, lidocaine enhanced IFN-γ production in sorted CD8+ TIICs through G-protein-coupled receptor (GPCR) signaling and increased IL-12 production in sorted CD14+ TIICs via the toll-like receptor 4 (TLR4) signaling pathway. Lidocaine also increased IFN-γ production and cytotoxicity in CD8+ TIICs via NF-κB activation. Importantly, lidocaine did not affect the viability of PBMCs, TIICs, or PGCCs at concentrations up to 1.5 mM. Lidocaine reprogrammed the tumor immune microenvironment, enhancing anti-tumor immune responses, suggesting its potential to modulate immune functions in gastric cancer.